Keberkesanan Program Pengembangan Pertanian di Malaysia : Kajian Kes Projek Limau Bali (Citrus Grandis L) di Daerah Kubang Pasu Negeri Kedah Darul Aman - Mahyuddin (2012)
Agricultural extension is the process of informal education in the context of agricultural technology transfer. It is carried out systematically to help farmers to improve their socio-economic achievements. Malaysian Fruit Crops Statistics 2002 showed that there are 686.20 hectares of Pomelo crops in Kedah but only 340.80Ha has released the output about 1,445.90 metric tons (RM 3,232,076.00). Kedah Agriculture Department has undertaken restoration crops through Agricultural Extension Programs to increase Pomelo crop yields. Therefore, a qualitative study through interviews, observations and visits carried out to investigate: (i) definitions, concepts, philosophy and structure of Agriculture Extension Service in Malaysia; (ii) to what extent the Restoration Project and Planting Pomelo at Kubang Pasu in raising contributions for National food availability; (iii) to what extent of implementation of the planning, monitoring and methods in Agriculture Extension Program in Malaysia; and (iv) the strengths, weaknesses, opportunities and threats in the Restoration and Planting Project in Kubang Pasu. In general, the results showed that the implementation of the program is very good. The results from SWOT analysis and TOWS matrix suggest the improvements of Extension Program in Restoration and Planting Pamelo Project.